2017
DOI: 10.3332/ecancer.2017.750
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative radiotherapy: review of techniques and results

Abstract: Intraoperative radiotherapy (IORT) is a technique that involves precise delivery of a large dose of ionising radiation to the tumour or tumour bed during surgery. Direct visualisation of the tumour bed and ability to space out the normal tissues from the tumour bed allows maximisation of the dose to the tumour while minimising the dose to normal tissues. This results in an improved therapeutic ratio with IORT. Although it was introduced in the 1960s, it has seen a resurgence of popularity with the introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 175 publications
(208 reference statements)
0
59
0
13
Order By: Relevance
“…During this period, residual tumor cells may be able to re-grow and/or migrate and on, the long run, cause local relapses. In this regard, IORT offers the advantage of instantaneous "sterilization" of the tumor bed, which was proven to be highly efficient in a wide variety of intra-abdominal tumours, recurrent colorectal cancers, recurrent gynaecological cancers, and soft-tissue tumours breast cancer, brain tumors and soft-tissue sarcoma [17][18][19][20]. A number of mono-institutional trials demonstrated improved local control of rectal cancer after IORT even in the era of neoadjuvant therapy [10], whereas specifically patients with microscopically-involved circumferential resection margins (CRM) may benefit most [9,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…During this period, residual tumor cells may be able to re-grow and/or migrate and on, the long run, cause local relapses. In this regard, IORT offers the advantage of instantaneous "sterilization" of the tumor bed, which was proven to be highly efficient in a wide variety of intra-abdominal tumours, recurrent colorectal cancers, recurrent gynaecological cancers, and soft-tissue tumours breast cancer, brain tumors and soft-tissue sarcoma [17][18][19][20]. A number of mono-institutional trials demonstrated improved local control of rectal cancer after IORT even in the era of neoadjuvant therapy [10], whereas specifically patients with microscopically-involved circumferential resection margins (CRM) may benefit most [9,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Although 2 randomized trials revealed no LRR or OS benefit with the addition of IORT, a pooled retrospective analysis of over 600 patients reported that IORT significantly reduced LRR rates in patients who underwent margin‐positive resection . Complication rates with IORT ranged from 5% to 60%, including wound complications in up to 40% of patients and gastrointestinal fistulae and ureteral injury in 2% to 12% …”
Section: Rectal Cancermentioning
confidence: 99%
“…22 Complication rates with IORT ranged from 5% to 60%, including wound complications in up to 40% of patients and gastrointestinal fistulae and ureteral injury in 2% to 12%. 23 Despite the notable advances in surgical and adjuvant therapy over the past few decades, LRR rates for rectal cancers remain between 4% and 8%, and the more extensive surgery and adjuvant therapies all come with increased patient morbidity. Without treatment, patients with LRR experience a shortened life expectancy and often a poor quality of life.…”
Section: Rectal Cancermentioning
confidence: 99%
“…IORT quickly became adopted worldwide despite the technical challenges ( 2 , 7 – 10 ) but became less used once IR equipment manufacturers ceased engaging in customized instrument changes. A recent resurgence of this treatment modality can probably be credited to the development of new types of IORT dedicated radiation devices such as mobile linear accelerators ( 11 ) and specially designed applicators for positioning of high activity radioactive sources ( 12 ). Thus, although current medical device regulations prevent in-house development of IORT accelerators—a problem that slowed this field until recently, the availability of commercial devices obviated this necessity.…”
Section: Intraoperative Radiation Therapy (Iort) Todaymentioning
confidence: 99%